STRENGTH-BASED PARENTING, SELF-COMPASSION, AND THE URGE TO SELF-INJURE IN UNIVERSITY STUDENTS - Sumargi, Agnes Maria; Engry, Agustina; Julianti Ratna, Josephine Maria; Variani, Joana (Jurnal Psikologi, 2022)
University students might experience emotional problems leading to self-injury during the COVID-19 pandemic due to negative relationships with their parents at home. However, strength-based parenting (SBP) can be a protective factor for self-injury. Previous studies showed that SBP had a positive correlation with self-compassion, but no study investigated the effect of SBP and self-compassion on the urge to self-injure. This present study aimed to examine if self-compassion mediated the relationship between SBP and the urge to self-injure. Participants were 193 university students in Surabaya aged 18-21 years old (M = 19.92; SD = 1.21), 86.5% was female. They were recruited voluntarily and asked to complete a series of questionnaire online, consisting of the Strength-Based Parenting Scale, Self-Compassion Scale, and the Alexian Brothers Urge to Self-Injure Scale. Mediation analysis was performed using PROCESS Macro for SPSS. Result showed that SBP was not directly related to the urge to self-injure, t(190) = 0.84, p = .40 (ns), but self-compassion mediated the relationship, ab = -0.93 [-1.30, -0.57]. SBP positively influenced self-compassion, a = 0.17, t(191) = 5.70, p < .001, and self-compassion negatively influenced the urge to self-injure, b = -5.49, t(192) = -8.74, p < .001. Further exploration revealed that self-judgment and over-identification influenced the urge to self-injure, t(186) = -3.35, p < .01 and t(186) = -1.98, p < .05, respectively. Therefore, self-compassion trainings and activities to reduce self-criticism and to identify negative thoughts or feelings might play an important role in preventing and overcoming the urge to self-injure in university students.